2014
DOI: 10.1097/brs.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Risk Factors for 30-Day Unplanned Readmissions After Lumbar Spine Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
148
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 26 publications
9
148
3
Order By: Relevance
“…We recommend that future studies examine the benefits of close monitoring and rigorous followup on the readmission rate of patients with extended lengths of stay. The correlation of ASA score to increased 30-day readmissions aligns with results reported in the orthopaedic spine literature [3,16,23,25]. We believe that an increased ASA score aligns with increased comorbidities, thus increasing the likelihood of 30-day readmission.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We recommend that future studies examine the benefits of close monitoring and rigorous followup on the readmission rate of patients with extended lengths of stay. The correlation of ASA score to increased 30-day readmissions aligns with results reported in the orthopaedic spine literature [3,16,23,25]. We believe that an increased ASA score aligns with increased comorbidities, thus increasing the likelihood of 30-day readmission.…”
Section: Discussionsupporting
confidence: 86%
“…This is low compared with other orthopaedic studies [9,27]. As we would expect with a low incidence of surgical readmission, our medical 30-day readmission rate of 42% is high when compared with other studies [18,20,23]. The most common cause of surgical readmission is surgical site infection.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The most common etiology was wound complications (38.6%), including superficial and deep infection, hematoma, or seroma development. 113 In neurosurgery-specific data, a study of 4970 patients undergoing lumbar spine surgery in the N 2 QOD registry demonstrated an overall 30-day readmission rate of 3.7%, with a 90-day readmission rate of 8.9%. 9 Read-missions varied by pathology and operation, with 2.4% of patients with disc herniation, 3.4% of patients with spondylolisthesis, and 4.9% of patients with spinal stenosis requiring readmission within 30 days.…”
Section: Rationalementioning
confidence: 99%
“…Wound infection was found to be the most common precipitating event (38.6%) of 30-day readmissions in the 2012 ACS NSQIP data for 15,668 patients undergoing lumbar spine surgery. 113 The National Healthcare Safety Network (2006)(2007) demonstrated an SSI rate of 2.8%-9.7% for spine surgery. 37 Given the magnitude and the potential impact of postoperative infections on spine patients, establishing process measures to, in part, prevent these complications is of paramount importance.…”
Section: Rationalementioning
confidence: 99%